Fabrication of green dye-sensitized solar cell based on ZnO nanoparticles as a photoanode and graphene quantum dots as a photo-sensitizer - Zamiri, Golnoush; Bagheri, Samira (Elsevier, 2018)
Zero-dimensional graphene quantum dots (GQDs) consist of single- or few-layer graphene with a size less than 20 nm and stand for a new type of QDs with unique properties combining the graphene nature and size-resulted quantum effects. GQDs possess unique optical and electronic properties, and in particular possess a band-gap less than 2.0 eV because of quantum confinement and edge effects. In this study, we investigated the performance of DSSCs using different thicknesses of ZnO nanoparticles as a photo-anode and GQDs as a green photosensitizer. The current voltage (I-V) test results indicate that the performance of DSSCs is improved by increasing the thickness of the photo-anode and the thickness of 40 μm shows the highest efficiency for DSSC device based on ZnO nanoparticles photo-anodes. The DSSC using ZnO nanoparticles as a photo-anode with thickness of 40 μm shows almost same efficiency when we replaced N-719 with GQDs which is confirmed that using GQDs as an alternative to ruthenium based dyes is a new approach for DSSCs.